The public health nurse history in Spain - Javier Gómez Robles; Manuela Domingo Pozo (Universidad de Alicante, 1999)
In Spain, at present does not exist the figure of the Public Health Nurse Specialist, although the creation of such a career speciality was taken into consideration by Law in 1987 (R.D: 992/1987). Nevertheless, the situation was somehow different in the first years of our century when the so called "Visitadora Sanitaria" (similar to District Nurse) was a nurse with a different education to those engaged in hospital clinical work or "practicantes", and who regarded health problems from a wider perspective: with a community vision. Why has such a figure not evolved into a Community Nursing Specialist?. Our primary aim here is to provide a global vision of Public Health Nursing starting from its origins in Great Britain and in the U.S.A. and focusing later on the evolution of this important figure in Spain.